PSMP Is Discriminative for Chronic Active Antibody-Mediated Rejection and Associate With Intimal Arteritis in Kidney Transplantation - Zhan, Panpan; Li, Haizheng; Han, Mingzhe; Wang, Zhen; Zhao, Jie; Tu, Jinpeng; Shi, Xiaofeng; Fu, Yingxin (Frontiers in Immunology, 2021)
Chronic active antibody-mediated rejection (CAAMR) is an intermediate process that occurs during the development of chronic antibody-mediated rejection (CAMR), which is a key problem associated with the long-term kidney grafts survival. This study investigated the role played by PC3-secreted microprotein (PSMP) in the progression of CAAMR and CAMR. We showed that CAAMR and CAMR patients’ allografts were disfunction with declined survival rate, which suggested that earlier diagnosis and treatment of CAAMR might be important to prevent irreversible chronic injury of CAMR progression. We found PSMP was an important factor in the development of chronic antibody-mediated rejection. The PSMP expression increased significantly in CAAMR biopsy samples but not in CAMR and control patients, that distinguished CAAMR patients from CAMR and non-rejection patients. Moreover, our results showed that infiltration of CD68+ macrophages in CAAMR increased, and the correlation between CD68+ macrophages and PSMP expression in CAAMR patients was significant. Additionally, our data also revealed that intimal arteritis (v-lesion) accompanied by increased macrophage infiltration might contributed to more graft loss in CAAMR, and PSMP expression was significantly associated with the v-lesion score. These results indicated that PSMP played an important role in the recruitment of macrophages and promote intimal arteritis inducing allograft lost in CAAMR progression. In future study PSMP could be a potential histopathological diagnostic biomarker and treatment target for CAAMR in kidney transplantation.